THU0193 Efficacy and safety of bcd-055 (INFLIXIMAB BIOSIMILAR) in rheumatoid arthritis. results of bcd-055–3/lira phase 3 clinical study. (12th June 2018) - Lila, A.; Denisov, L.; Plaksina, T.; Smakotina, S.; Kunder, E.; Soroka, N.; Kastanayan, A.; Nesmeyanova, O.; Antipova, O.; Ilivanova, E.; Eremeeva, A.; Dokukina, E.; et al.
Abstract : Background: Equivalent efficacy of BCD-055 and infliximab (INF) innovator has been previously established (the primary endpoint: ACR20 at Wk14) 1 . Objectives: The impact of BCD-055 and INF innovator on RA activity has been analysed within 14 week study period. DAS28-CRP(, 4 CDAI and SDAI were evaluated. Additionally, safety data has been collected. Methods: The study was conducted as international multicenter randomised double-blind placebo controlled study. The study enrolled 426 adults with active RA. Patients were randomised into 2 study arms in 2:1 ratio to receive BCD-055 or INF innovator in dose of 3 mg/kg. In the analysed period of the study, patients received the iv infusions on Wk0, Wk2, Wk6, Wk14. Results: Efficacy: BCD-055 and INF innovator showed similar impact on RA activity: in both groups significant decline of DAS28-CRP( 4 was observed (figure 1). This result corresponds to positive CDAI and SDAI dynamics (table 2). Medians of CDAI/SDAI on screening indicated high RA activity, while on Wk 14 – moderate activity. Analyses of inflammatory markers (ESR and C-reactive protein) revealed pronounced decline in ESR and CRP levels by Wk 2. No further elevation has been observed. Safety: No differences in safety profiles of BCD-055 and INF innovator has been shown. One of the most frequent AEs were arterial hypertension, anaemia, neutropenia and increase of transaminases. Number of patients with binding and neutralising antibodies also did not differ between groups. Babs were detected in 6.83% patients in BCD-055 arm and in 7.81% in INF innovator arm (p=0.888), Nab were observed in 1.61% and 0.78% patients in same arms (p=0.666). Conclusions: Treatment with BCD-055 and INF innovator leads to significant decline in RA activity and inflammatory markers by Wk14, which corresponds with previous results of ACR20 assessment1. Both drugs are well tolerated with no differences in safety profiles. The frequency of ADA formation is also comparable. Reference: [1] Denisov L, Gordeev I, Mazurov V, et al. FRI0208 Comparison of efficacy, safety and pharmacokinetics of infliximab biosimilar (BCD-055) and innovator infliximab Ann Rheum Dis2017;76:560–561. Disclosure of Interest: A. Lila: None declared, L. Denisov: None declared, T. Plaksina: None declared, S. Smakotina: None declared, E. Kunder: None declared, N. Soroka: None declared, A. Kastanayan: None declared, O. Nesmeyanova: None declared, O. Antipova: None declared, E. Ilivanova: None declared, A. Eremeeva Employee of: JSC BIOCAD, E. Dokukina Employee of: JSC BIOCAD, E. Chernyaeva Employee of: JSC BIOCAD, R. Ivanov Employee of: JSC BIOCAD